(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Three-dimensional (3D) printed phantoms are a cost-effective way for quality control of imaging devices. Here we evaluate two 3D printed versions of the NEMA NU 4-2008 phantom for small animal positron emission tomography (PET), compared to a phantom made of PMMA. The behavior of the materials is analyzed using PET for two radiotracers with different positron ranges, as well as the compatibility of the phantoms with MRI. In conclusion, image degradation due to positron range is more pronounced for the material E-Shell 600 clear. Some support materials required by 3D printing can produce artifacts in MRI images.